Religious-Magic Issue Lubuk Larangan Datuk Rajo Temanggung Double Effect; Environmental Preservation, Law Enforcement, Preserved Customs, Religion Is Maintained, Life (Economy) Develops - Syamsul Huda; Bawaihi; Ida Rianty; Ahmad Wahyudi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Lubuk Larangan is an area for the protection and conservation of fishery resources in a village area where the utilization regulation is based on the interests of the village by taking into account the principles of benefits, fairness, efficiency and sustainable sustainability. The purpose of this study was to analyze the Lubuk Ban village of Muara Cuban from five perspectives. This research method isusing a type of literature review research by looking for theoretical references that are relevant to the cases or problems found. Communities have their own ways and provisions in managing lubukban which are adapted to the customary rules and culture of the local community. It is very important for traditional communities to be involved in the conservation of aquatic resources. Traditional wisdom is one of the cultural heritages that exist in the community (traditional) and has been passed down from generation to generation by the community concerned. Forbidden pitDatuk Rajo Temanggung this is a togetherness event as well as an event to maintain friendship so that it is always good among the people of Muara Cuban Village, mthey met in this lubuk ban harvesting event, sosocial interaction takes place in the form of communication, cooperation, and helping each other which makes them closer regardless of social status. In accordance with a mutual agreement with the community, Lubuk Larangan is harvested simultaneously in 6 lubuks (Lubuk Mentaun, Lubuk Palipe Telun Segatal, Lubuk Telun Beringin, Lubuk Mendapo, Lubuk Betung, Lubuk Aro). Then the community can participate in the harvesting process. Catching fish with simple tools such as fishing rods, fish traps, gitang, pukek and jalo.